Performance at Enade and the conditions of educational process from Accounting Sciences students - Meurer, Alison Martins; Pereira, Victor Hugo (Contextus - Revista Contemporânea de Economia e Gestão, 2020)
The research aims at analyzing the relationship between the likelihood of high performance at Enade and the conditions of the educational process from Accounting Sciences students, considering 25,998 participations in Enade in 2018 and with the aid of exploratory factor analysis and logit regression. Thus, students with higher levels of satisfaction with the didactic-pedagogical organization and with the infrastructure of educational institutions are more likely to achieve higher performance at Enade. The variables graduation in public HEI, presential modality, male gender, father and mother with higher education and free higher education also maximize the performance of students. The opportunities to expand academic and professional training, older age and not working reduce the likelihood of high performance.